Inequality of household consumption and air pollution-related deaths in China - Hongyan Zhao (Nature Portfolio, 2019)
Considering air pollution-induced health risks from a consumption perspective is important. Here the authors evaluated the premature deaths resulting from household consumption across 30 Chinese provinces and find that rural households can cause a similar number of pollution-induced deaths as urban households despite a larger and wealthier urban population, due to the combustion of solid fuel.